2020
DOI: 10.1039/d0ma00406e
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport in a sequentially doped naphthalene diimide polymer

Abstract: Sequential doping of PNBS, notably with (N-DMBI)2, is studied using UV-vis.-NIR spectroscopy, GIXRD, and variable-temperature conductivity measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…However, PDFD-T(L) exhibited a much lower µ Hall value of 0.65 cm 2 V −1 s −1 due to the formation of disordered charge transport pathways after doping. [46,47] The dependence of carrier mobility on the molecular weight is supported well by the microstructure analysis results obtained from the GIWAXS measurements (vide infra). Based on these observations, it can be concluded that, for achieving high σ levels, high molecular weight is crucial in maintaining excellent charge transport properties and higher doping levels.…”
Section: Uv-vis-nir Absorption Spectra and Charge Carrier Mobility Me...supporting
confidence: 56%
“…However, PDFD-T(L) exhibited a much lower µ Hall value of 0.65 cm 2 V −1 s −1 due to the formation of disordered charge transport pathways after doping. [46,47] The dependence of carrier mobility on the molecular weight is supported well by the microstructure analysis results obtained from the GIWAXS measurements (vide infra). Based on these observations, it can be concluded that, for achieving high σ levels, high molecular weight is crucial in maintaining excellent charge transport properties and higher doping levels.…”
Section: Uv-vis-nir Absorption Spectra and Charge Carrier Mobility Me...supporting
confidence: 56%
“…VPI with TiCl 4 + H 2 O also alters the electrical conductivity (σ) of the PAni films. The electrical conductivity in chemically doped semiconducting polymers is a function of both carrier concentration and carrier mobility, but the mathematical relationship among conductivity, mobility, and carrier concentration is nontrivial because polymers are spatially and energetically inhomogenous. ,, Figure plots the electrical conductivity of PAni hybrid films as a function of the precursor exposure time (measured immediately upon removal from the VPI chamber using a four-point probe technique). The electrical conductivities of pristine PAni thin films are not measurable with our experimental setup and film thicknesses (σ < ca.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the electronic conductivities of the NDI-functionalized biopolymer, either before the reduction of NDI (B4 mS cm À1 ) or after the reduction (B40 mS cm À1 ), are on the higher end of conductivity values compared to those of other NDI-based polymers. 42,43,[47][48][49][50][51][52][53][54] We attribute the high conductivity of the NDI-functionalized BSA biopolymer to our chemical attachment strategy, targeting the many carboxylic acid-containing residues on the surface of the protein composing the biopolymer. As a result, we suggested that the NDI monomers adopt face-to-face packing which promotes the efficient electronic transport along the biopolymer.…”
Section: Discussionmentioning
confidence: 99%